FACTORS AFFECTING SAFE SEX PRACTICES AMONG FIRST YEAR STUDENTS AT THE UNIVERSITY OF NAMIBIA: A HEALTH BELIEF MODEL PERSPECTIVE - Gert Van Rooy; Pempelani Mufune; Nelago Indongo; Kenneth Matengu; Erica Libuku; Christa Schier (European Scientific Journal, ESJ, 2014)
The aim of the study was to investigate the level of awareness of condom usage among first year’s students at the University of Namibia. Data was collected among 578 students within the various disciplines of the university through self-administered questionnaires that tested their knowledge, attitude and beliefs regarding HIV and AIDS. Research assistants were at hand clarifying ambiguities during the completion of the questionnaire. To ensure a good response rate, the researcher arranged with lecturers for students to complete questionnaires during lecture periods. A multi-stage sampling technique was used - in the first instances the number of campuses were purposefully recorded and stratified in accordance with the subjects offered and then students were randomly selected from the various faculties. Data was analysed using SPSS version 21. Results indicate that 80.1 % of the students are using condoms with their partner (s) while 76.3% used a condom during the past 12 month’s preceding the survey.